1993
DOI: 10.1212/wnl.43.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Pick's disease versus Alzheimer's disease

Abstract: The clinical recognition of Pick's disease depends on its differentiation from Alzheimer's disease (AD). To identify distinguishing clinical features, we reviewed the clinical records of 21 patients with pathologically confirmed Pick's disease and matched them by sex, age of onset, and duration of dementia with 42 patients having pathologically confirmed AD. In the absence of temporal or frontal lobar atrophy on CTs, all the Pick patients and none of the AD patients had three of five clinical features: preseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1
7

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(117 citation statements)
references
References 0 publications
2
107
1
7
Order By: Relevance
“…Differentiation between FTD and AD during life can be problematic, however, because both disorders have an insidious onset, produce a progressive dementia syndrome that can include executive dysfunction and language impairment, and can cause alterations in behavior (Mendez et al, 1993). Consequently, despite the careful application of the Neary criteria (Neary et al, 1998), some subjects might have been misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation between FTD and AD during life can be problematic, however, because both disorders have an insidious onset, produce a progressive dementia syndrome that can include executive dysfunction and language impairment, and can cause alterations in behavior (Mendez et al, 1993). Consequently, despite the careful application of the Neary criteria (Neary et al, 1998), some subjects might have been misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Although histopathologically distinct from the more common Alzheimer's disease (AD), FTD is often difficult to differentiate from probable AD during life (Litvan et al, 1997;Mendez et al, 1993;Varma et al, 1999). Accurate differential diagnosis is crucial, however, given potential differences in prognosis (Rascovsky et al, 2005) and in pharmacological management strategies that might be suggested by different neurotransmitter system involvement in the two disorders Moretti et al, 2003;Pasquier et al, 2003;Qume et al, 1994;Rahman et al, 1999;Sparks & Markesbery, 1991;Swartz et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This has lead to a better distinction of FTD from AD, which is the most frequent misdiagnosis of FTD. 3,4 Recently, mutations in the tau gene localised to 17q21 have been identified in several families with autosomal dominant inheritance. 5 -8 To date, ten missense mutations, two deletions, and three transition mutations not altering the encoded amino-acid sequence have been identified in exons of the tau gene.…”
Section: Introductionmentioning
confidence: 99%